2022
DOI: 10.3390/insects13050399
|View full text |Cite
|
Sign up to set email alerts
|

Perennial Flowering Plants Sustain Natural Enemy Populations in Gobi Desert Oases of Southern Xinjiang, China

Abstract: Natural habitats play crucial roles in biodiversity conservation and shape the delivery of ecosystem services in farming landscapes. By providing diverse resources to foraging natural enemies, they can equally enhance biological pest control. In this study, we described the plant community and foliage-dwelling invertebrate predators within non-crop habitats of the Gobi Desert oases in southern Xinjiang, China. We assessed whether plant-related variables (i.e., species identity, flowering status) and herbivore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Although Aphis gossypii is a polyphagous pest, they primarily cause severe damage only to cotton plants. Around cotton fields, there are other host crops such as fruit trees, corn, and wheat, [73][74][75] but Aphis gossypii poses minimal threat to these crops. Additionally, around cotton fields there are untilled areas dominated by weeds that are suitable hosts for Aphis gossypii.…”
Section: Discussionmentioning
confidence: 99%
“…Although Aphis gossypii is a polyphagous pest, they primarily cause severe damage only to cotton plants. Around cotton fields, there are other host crops such as fruit trees, corn, and wheat, [73][74][75] but Aphis gossypii poses minimal threat to these crops. Additionally, around cotton fields there are untilled areas dominated by weeds that are suitable hosts for Aphis gossypii.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of non-crop habitats surrounding or within arable land has been associated with increasing arthropod NEs of pests by providing floral resources, thus sustaining their populations [ 25 , 26 ]. For instance, important NEs such as parasitoids use nectar to fulfil their nutrition requirements at some stages of their development while spiders, lady beetles, rove beetles, syrphid flies, true bugs and lacewings use non-crop habitats to provide them with refuge, alternative hosts, pupation and overwintering sites [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. It has been found that populations of NEs in field crops decline as the distance from the field margin increases and this demonstrates the essential function of field margins in maintaining NEs [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of noncrop habitats surrounding or within arable land has been associated with increasing arthropod NEs of pests by providing floral resources and sustaining their populations (Chaplin-Kramer et al, 2011;González et al, 2022). For instance, spiders, lady beetles, rove beetles, syrphid flies, true bugs and lacewings use non-crop habitats to provide them refuge, alternative hosts, pupation and overwintering sites (Baggen & Gurr, 1998;Bianchi et al, 2006;Chaplin-Kramer et al, 2011;González et al, 2022;Landis et al, 2000;Long et al, 1998;Liu et al, 2022;Nicholls et al, 2001;Olson & Wäckers, 2007;Pywell et al, 2005;Thies & Tscharntke, 1999;Thomson & Hoffman, 2009;. However, floral resources provide different benefits to specific taxa of NEs (Wäckers, 2004) and thus NEs would respond differently to the proportions of non-crop habitats.…”
Section: Discussionmentioning
confidence: 99%